Eurasian beaver (Castor fiber) health surveillance in Britain: Assessing a disjunctive reintroduced population. (2nd February 2021) - Campbell‐Palmer, Róisín; Rosell, Frank; Naylor, Adam; Cole, Georgina; Mota, Stephanie; Brown, Donna; Fraser, Mary; Pizzi, Romain; Elliott, Mark; Wilson, Kelsey; Gaywood, Martin; Girling, Simon
Abstract: Background : Numerous translocations of Eurasian beavers have occurred with little implementation of standardised health screening. Pre‐release health screening enables the selection of individuals with the best survival prospects and reduces potential health risks, but this is by‐passed during unofficial releases. Beaver reintroduction to Britain has been haphazard and currently disjunctive populations of varying status exist. Methods : This observational cross section study investigated the health status of three beaver populations, with 90 live beavers tested for a range of pathogens comprising 56 from Tayside (unofficially released Scotland), nine from Knapdale (officially released Scotland) and 25 from Devon (unofficially released England). In addition, a further 32 cadavers were screened (25 from Tayside and seven from Knapdale). Results : All beavers were in good physical condition, did not harbour any non‐native disease or parasites of concern and demonstrated remarkably low levels of any disease or parasite exposure. Conclusion : Beavers are establishing and adapting well to British landscapes and are not acting as reservoirs of significant zoonotic diseases. Official, licensed reintroduction programmes may appear overly convoluted; however, reputational damage of unofficial releases should be considered, along with the health and welfare of the animals involved and collateral damage to other wildlife, domestic animals and humans.